PENERAPAN MODEL INDEX CARD MATCH DALAM UPAYA MENINGKATKAN PEMAHAMAN KONSEP PERKALIAN DENGAN BANTUAN MEDIA - Almira Amir (Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Padangsidimpuan, 2021)
AbstractThe background of this research is the low understanding of students' concepts in mathematics for multiplication material. Students find it difficult to understand the concept of multiplication and apply it in everyday life. Inappropriate learning strategies and the absence of media use are one of the causes of students' low understanding of the concept of multiplication material. The purpose of this study was to improve students' conceptual understanding of multiplication material by applying the Index Card Match model with the help of learning media at MIN 2 Padangsidimpuan. The learning media used is the rule of thumb. This research is a classroom action research which consists of two cycles and each consists of four main activities, namely planning, action, observation, and reflection. The subjects of this study were students of class IV MIN 2 Padangsidimpuan, totaling 30 people. The instrument for collecting data was a test sheet to measure students' conceptual understanding and an observation sheet to observe learning activities using the Index Card Match model with the help of learning media. Based on the results of the study, it was found that students' conceptual understanding increased in multiplication material through the Index Card Match learning model with the help of learning media, this can be seen from the increase in students' concept understanding test results where the average test increased, namely in the initial test 54.67 increased to 55.17 in the first cycle test 1 meeting and 59.33 in the first cycle test meeting 2. In the second cycle there was an increase of 65.00 in the second cycle meeting 1 and increased to 71.83 in the second cycle meeting 2. Keywords: Concept Understanding, Index Card Match Learning Model, Learning Media. AbstrakPenelitian ini dilatarbelakangi oleh rendahnya pemahaman konsep siswa pada materi perkalian. Siswa kesulitan memahami konsep perkalian dan menerapkannya dalam kehidupan sehari-hari. Strategi pembelajaran yang tidak tepat dan tidak adanya penggunaan media menjadi salah satu penyebab rendahnya pemahaman siswa terhadap konsep materi perkalian. Tujuan penelitian ini adalah untuk meningkatkan pemahaman konsep siswa pada materi perkalian dengan menerapkan model Index Card Match dengan bantuan media pembelajaran di MIN 2 Padangsidimpuan. Media pembelajaran yang digunakan adalah rule of thumb. Penelitian ini merupakan penelitian tindakan kelas yang terdiri dari dua siklus dan masing-masing siklus terdiri dari empat kegiatan utama, yaitu perencanaan, tindakan, observasi, dan refleksi. Subyek penelitian ini adalah siswa kelas IV MIN 2 Padangsidimpuan yang berjumlah 30 orang. Instrumen pengumpulan data berupa lembar tes untuk mengukur pemahaman konsep siswa dan lembar observasi untuk mengamati aktivitas pembelajaran menggunakan model Index Card Match dengan bantuan media pembelajaran. Berdasarkan hasil penelitian diketahui bahwa pemahaman konsep siswa meningkat pada materi perkalian melalui model pembelajaran Index Card Match dengan bantuan media pembelajaran, hal ini terlihat dari peningkatan hasil tes pemahaman konsep siswa dimana rata-rata tes meningkat yaitu pada tes awal 54,67 meningkat menjadi 55,17 pada tes siklus I pertemuan 1 dan 59,33 pada tes siklus I pertemuan 2. Pada siklus II terjadi peningkatan 65,00 pada siklus II pertemuan 1 dan meningkat menjadi 71,83 pada pertemuan siklus II. Kata Kunci: Pemahaman Konsep, Model Pembelajaran Index Card Match, Media Pembelajaran